A Behavioral-Analytic Model for Assessing Stress in Firefighters. Issue 2 (March 2022) - Schuhmann, Bailee B.; Henderson, Sarah N.; Black, Ryan A.; Van Hasselt, Vincent B.; Klimley Margres, Kristin; Masias, Estefania V.; LeDuc, Todd J.
Research has documented a number of acute and chronic stressors unique to the fire service. Due to the rise in mental health concerns in firefighters, there has been increased awareness of the negative effects of unmanaged stress. The present study employed a behavioral-analytic model to construct a brief screening measure of stress for this population: the Firefighter Assessment of Stress Test (FAST). Psychometric properties of the FAST were evaluated using data from active-duty firefighters throughout the United States. Results indicated the FAST has good internal reliability ( α = 0.89), as well as good convergent and discriminant validity. Also, the factor structure of the FAST revealed three significant subscales reflective of stress associated with responding to calls, administrative difficulties, and being overworked. Scoring and interpretation guidelines were established to suggest when further assessment is warranted. The FAST offers a brief and valid method of self-assessment of current stress levels in firefighters. Information obtained from the FAST (i.e., overall stress level and domains) has the potential to facilitate more immediate identification and recognition of stress in firefighters than what has been possible to date. Moreover, heightened awareness of stress and its effects will hopefully culminate in expanded efforts directed toward stress reduction and intervention for firefighters and their families.